A freaky motorbike accident causing vulvar hematoma: a case report at the Bafoussam Regional Hospital, West-Cameroon - Fouogue, Jovanny Tsuala; Fetse, Gerard Tama; Kenfack, Bruno; Fouedjio, Jeanne Hortence; Foueifack, Florent Ymele; Nganwa, Grace Kembaou; Noubom, Michel; Orock, Georges Enow; Sando, Zacharie; Kemfang, Jean Dupont Ngowa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Non-obstetric vulvar hematomas are rare and have never been reported in West Cameroon. No guidelines are available to inform the management of cases. Authors herein report the successful management of a post-traumatic vulvar hematoma in a 17 years old gravida 1 para 1001 patient. She was referred to our emergency department ten hours after a fall in a squatting position during a road traffic accident. Prior to the referral she had been managed conservatively by analgesics and a compressive dressing of the vulva in a community clinic. Clinical assessment on admission revealed a good general condition, normal vital signs and a tense and painful hematoma of the right labia. Surgery was done under general anesthesia to drain the hematoma, ligate the bleeding vessels and repair the vulva. Post-operative course was uneventful and the patient was discharge six days later. This case reminds practitioners in remote health facilities that early referral of this rare pathology contributes to its successful surgical management in our semi-urban region.